Analysis of Concession, Technology, and Service Implementation on Port Infrastructure Performance: A Case Study in DKI Jakarta and Banten Provinces - Amsyari, Isa; Gautama So, Idris; Abidin, Zaenal; Priadi, Antoni Arif (Jurnal Penelitian Transportasi Laut, 2024)
As an archipelagic country, Indonesia relies heavily on ports as the main infrastructure to support the national logistics system and international trade. Despite its importance, port management in Indonesia faces challenges such as lack of government support, corruption, bureaucratic inefficiency, and gaps between policy and implementation. This study aims to analyze the effect of concession implementation, technology utilization, and port services on the role of Port Business Entities (BUP) and their impact on port infrastructure performance in DKI Jakarta and Banten Provinces. The study used a quantitative method with a Likert scale questionnaire based on 31 indicators covering five variable constructs: concession implementation, technology utilization, port services, BUP role, and port infrastructure performance. Data were collected from 310 respondents selected through stratified sampling, consisting of users of port services managed by BUP from November 2023 to January 2024. Data analysis was carried out using SmartPLS 3.2.9 software to validate the relationship between variables through the Structural Equation Modeling (SEM) approach. The results of the study indicate that concession implementation, technology utilization, and port services significantly influence the role of BUP, which in turn improves port infrastructure performance. In addition, the indirect influence of these variables reinforces the importance of strategic management and technology utilization in port optimization. This study confirms that implementing good concession policies, integrating modern technology, and improving port services can significantly improve the performance of port infrastructure in Indonesia. These findings provide important implications for policymaking and strategy development to optimize port operations in the future.